RELATIONSHIP AMONG MATERNAL, PRENATAL AND PREGNANCY OUTCOME IN RANGELI MUNICIPALITY OF NEPAL - Mahato, Asmita; Shrestha, Barsha (International Journal of Research -GRANTHAALAYAH, 2020)
Background: The incidence of pregnancy complications may be due to risk factors during pregnancy. Whether maternal parameters like age, gravida/ parity, gestational age, and fetal heart rate have any influence to the delivery outcome and newborn weight is a big quest. A young age at birth is more common in Nepal and carries a less social stigma, and hence enforces this study to understand the impact. Objective and methodology: The objectives of this retrospective study were to evaluate the maternal and prenatal outcomes of pregnancies and the effects of the age of the pregnancy, gravida, gestational age, and newborn weight. Pregnant women giving birth in Rangeli Hospital, Morang (Nepal) in 2019 were retrospectively screened. Pregnant women of all age group were included in this study. Results: Mean maternal age for delivery of child was 22.45 ±0.225 years. 41.9% of study subjects were primigravida (G1), while 58.1% were multi-gravida (G2-4). The mean age of primigravida is 20.57 ±0.025 years. Mean gestational week, fetal heart rate (FHR), and newborn weight were 38.18 ±0.11, 140.91 ±0.43, and 2870.65 ±26.13 g respectively. Almost one-third (32.1%) of the newborn were preterm babies. 20.9% of the newborn child was low birth weight. Spontaneous vaginal delivery was seen in 90.7% of the pregnancy while 7.9% had caesarean section. Conclusion: A significant positive correlation was seen of age with gravida, parity, and newborn weight. Newborn weight was significantly related to gestational age. There is no significant difference between the mean maternal age of mother delivering preterm baby or term-baby. No significant difference in the mean age of the mother or the mean gestational duration between male and female children could be established. Significant mean differences were seen in the maternal age of LBW child and normal birth weight child.